Vulvar varicosities: diagnosis, treatment, and prevention - Gavrilov SG (Dove Medical Press, 2017)
Sergey G Gavrilov Faculty of Medicine, Pirogov Russian National Research Medical University, Moscow, Russia Objective: Vulvar varicosity is a relatively common venous disorder in women with varicose veins of the pelvis and lower extremities and in pregnant women, but there is little information in the medical literature concerning its diagnosis and management. The aim of this study was to describe our experience with 101 women with vulvar varicosities who were examined and treated at our center during 2000–2014.Patients and methods: Patients were divided into two groups: group 1 with 61 women with varicose veins of the pelvis and enlarged vulvar veins, and group 2 with 40 pregnant women (11–38 weeks of pregnancy) with vulvar varicosities.Results: In most cases, vulvar varicosities were able to be diagnosed at clinical examination. In both groups, duplex ultrasound of the veins of the pelvis and lower extremities was used to confirm the presence of varicose veins, identify any retrograde flow, accurately determine vein diameter, and to reveal any anatomical feature of the intrapelvic veins. Treatment approaches varied significantly between the two groups from purely conservative measures during pregnancy to surgical procedures on the ovarian and vulvar veins in group 1. The venoactive agent, micronized purified flavonoid fraction, was effective at reducing the symptoms of vulvar varicosities in both groups.Conclusion: A tailored approach to the diagnosis and treatment of vulvar varicosities can significantly improve the quality of care of women with this disorder. Keywords: micronized purified flavonoid fraction, pelvic varicose veins, pelvic venous congestion, vulvar varicosities